(untitled) (Journal of Parents and Teachers, 2014)
Here is a letter from a father to his son when he asks for the umpteenth justification for not attending a religion class. In it, it is explained that religion is found in sciences, philosophy, art, and ultimately in the world, and that to know it is the basis of human intelligence and freedom.